PERAN KADER POS PELAYANAN TERPADU (POSYANDU) DALAM PENCEGAHAN STUNTING PADA ANAK USIA DINI DESA TELUK SIKUMBANG KECAMATAN MUARA SIAU KABUPATEN - Aminatu Zulfa; Jamilah; Amrindono (STKIP Subang, 2026)
The purpose of this study is to examine the role of Posyandu cadres in the prevention of stunting among early childhood in Teluk Sikumbang Village. This research employs a qualitative descriptive approach. The objectives of the study include: (1) to understand how Posyandu cadres contribute to stunting prevention among early childhood in Teluk Sikumbang Village, (2) to identify the challenges faced by Posyandu cadres in addressing stunting at the Posyandu, and (3) to determine the efforts made by Posyandu cadres in preventing and managing stunting at the Posyandu. The results of the study indicate that: (1) the role of Posyandu cadres is demonstrated through monitoring child growth, providing supplementary food, delivering nutrition education, reminding parents of Posyandu schedules and immunization, and collaborating with the village midwife to support optimal child development; (2) several challenges exist in the implementation of stunting prevention and management programs, including limited operational funds for Posyandu, inadequate supporting facilities, and low participation of some parents; and (3) the village midwife and Posyandu cadres have undertaken various efforts, such as raising awareness about the dangers of stunting to parents, providing nutrition education for pregnant and breastfeeding mothers, supplying supplementary food, promoting exclusive breastfeeding, administering complete immunizations, preventing and managing diarrhea, as well as reinforcing clean living habits and proper use of clean water in the community.